Effect of crude bacterial lipids on the course of Listeria infection in mice - Mára, M; Julák, J; Mencíková, E; Ocenásková, J; Dohnalová, A (Folia microbiologica, 1992)
Crude lipids from 37 strains belonging to 32 bacterial species were isolated. By injecting mice with lipids 5 d prior to challenge with a virulent strain of Listeria monocytogenes, immunostimulatory activity in 19 preparations was found. In general, lipids of Gram-negative bacteria appeared to be more effective. As to bacilli, an extraordinary activity was found in the lipids of Bacillus firmus. Lipids of various species of the genus Listeria were found to be active in approximately one-half of cases. Among other Gram-positive bacteria, significant activity of lipids was found in Corynebacterium xerosis, Propionibacterium acnes and BCG. The composition of fatty acids in the lipids did not differ significantly from that reported in the literature and their mutual differences could not explain the different biological activity. In selected strains of Gram-negative bacteria lipids were repeatedly purified with anhydrous chloroform; these preparations were found to be inactive as compared with original chloroform-methanol lipids.
Keywords: Lipids; Mice; Bacillus; adjuvancia imunologická; grampozitivní bakterie; Female; listeriové infekce; Bacteria; lipidy; Animals; ženské pohlaví; Gram-Positive Bacteria; Listeriosis; Listeria; zvířata; Adjuvants, Immunologic; myši; Enterobacteriaceae